IMPACT OF WORK MOTIVATION AND PEDAGOGIC COMPETENCY ON THE PERFORMANCE OF TEACHERS’ KINDERGARTEN IN BANDAR SRIBHAWONO, EAST LAMPUNG REGENCY - Nani Winayu; Siti Patimah; Ahiruddin Ahiruddin (Saburai International Journal of Social Sciences and Development, 2023)
The object of this research is a kindergarten teacher in Bandar Sribhawono District, East Lampung Regency. The problem in this study is that the performance of Kindergarten teachers in Bandar Sribhawono Sub-district is less than optimal due to the lack of compensation received by the teacher so that it interferes with the work motivation of teachers in teaching and problems in the form of lack of mastery of teaching materials and the lack of teacher ability in managing teaching and learning programs indicate the quality of kindergarten teacher performance is lacking. optimal. The purpose of this study was to determine the impact of work motivation and pedagogic competence on the performance of kindergarten teachers in Bandar Sribhawono District, East Lampung Regency. The type of this research is quantitative descriptive using population technique from all kindergarten teachers in Bandar Sribhawono District, East Lampung Regency as many as 69 teachers. The results of testing the hypothesis of the effect of work motivation (X1) on performance (Y) partially show that the t value of the work motivation variable is 4.500 with a constant of 3.052 in t table with 69 db and a significant level of 0.05 obtained 1.679 because t count t table then Ha is accepted, meaning that work motivation has a positive effect on the performance of kindergarten teachers in Bandar Sribhawono District, East Lampung Regency. teacher pedagogic competence while the remaining 76.9% is explained by other variables outside of this research variable. Testing the hypothesis of the effect of pedagogic competence on performance partially shows that the t value of the teacher pedagogical competence variable is 3,596 with a constant of 3.467 at t table with 69 db and a significant level of 0.05 obtained 1.679 because t count t table then Ha is accepted, meaning that pedagogical competence has an effect positive on the performance of kindergarten teachers in Bandar Sribhawono District, East Lampung Regency. Hypothesis testing simultaneously variable work motivation and variable pedagogic competence have a positive effect simultaneously (simultaneously) on performance. This can be seen from the calculated F value of 9936 which is greater than the f table of 3.204 The significance value of 0.000 which is smaller than 0.05 indicates that together work motivation and pedagogical competence have a positive and significant effect on the performance of Kindergarten teachers in Bandar Sribhawono District, District East Lampung.